Jerusalem: Points of Friction - And Beyond - Ma'oz, Moshe,; Nusseibeh, Sari, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The material in this publication was compiled over an 18-month period and includes a variety of local, national and international issues and disaggregating Jerusalem's intricate problems. It offers meaningful models that even though they may not yield solutions acceptable to all parties in the Israeli - Palestine conflict, will at least clearly demarcate common ground and draw the 'red lines' that may not (yet) be crossed. The result is an enormously valuable resource that cannot fail to attract the attention of anyone concerned with the future of the Mideast region.